Analisis Interaksi Senyawa Flavonoid Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Terhadap Aktivitas Enzim Glukosidase Secara In Silico Sebagai Anti Hiperglikemia - Keninten, Ida Surya Prabawa Satya; Arjita, I Putu Dedy; Saputra, I Putu Bayu Agus; Hermawati, Resna (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Diabetes mellitus is a condition of chronic hyperglycemia due to impaired insulin secretion. a-glucosidase is an enzyme on the surface of small intestinal epithelial cells that breaks down disaccharides or oligosaccharides into free monosaccharides, which then enter the bloodstream. This research used descriptive exploratory research through several stages including: ligand preparation, a-glucosidase enzyme preparation, Human Intestinal Absorption (HIA) test, Lipinski Rule of Five (Ro5) test, Prediction of Activity Spectra for Substance (PASS) test, molecular docking, and visualization of docking results. Data was analyzed by grouping values based on categories from the HIA test, Ro5 test, and PASS test. The docking results are analyzed by grouping the ligand models according to the energy and types of bonds formed. The results of the research showed that of the ten flavonoid compounds of bilimbi leaves (Averrhoa bilimbi L.) tested, the compounds quercetin/3,5,7,3',4'-pentahydroxyflavonone; 5,7,3',4',5'-pentahydroxyflavone; apigenin; retusin 7-o-neohesperidoside; and catechin 3-o-gallate/ epigallocatechin gallate has a binding affinity value for the activity of the a-glucosidase enzyme as antihyperglycemia. The compounds quercetin, 5,7,3',4',5'-pentahydroxyflavone, apigenin 7-cellobioside, catechin 3-o-gallate/epigallocatechin gallate are effective in the activity of the a-glucosidase enzyme as antihyperglycemia. Keywords: Flavonoids, Averrhoa Bilimbi L., a-glucosidase, In Silico, Anti Hyperglycemia  ABSTRAK Diabetes melitus merupakan kondisi hiperglikemia kronis akibat gangguan sekresi insulin. a-glukosidase merupakan enzim di permukaan sel epitel usus halus yang memecah disakarida atau oligosakarida menjadi monosakarida bebas, yang kemudian masuk ke aliran darah. Penelitian ini menggunakan deskriptif eksploratif dengan melalui beberapa tahap meliputi: preparasi ligan, preparasi enzim a-glukosidase, uji Human Intestinal Absorption (HIA), uji LipinskiRule of Five (Ro5), uji Prediction of Activity Spectra for Substance (PASS), molecular docking, dan visualisasi hasil docking. Data dianalisis dengan mengelompokkan nilai berdasarkan kategori dari uji HIA, uji Ro5, dan uji PASS. Hasil docking dianalisis dengan cara mengelompokkan model ligan yang memiliki energi dan jenis ikatan yang terbentuk. Hasil penelitian menunjukkan bahwa dari sepuluh senyawa flavonoid daun belimbing wuluh (Averrhoa bilimbi L.) yang diujikan, senyawa quercetin/3, 5, 7, 3’, 4’-pentahydroxyflavonone; 5, 7, 3’, 4’ ,5’-pentahydroxyflavone; apigenin; retusin 7-o-neohesperidoside; dan catechin 3-o-gallate/ epigallocatechin gallate memiliki nilai binding affinityterhadap aktivitas enzim a-glukosidase sebagai antihiperglikemia. Senyawa quercetin, 5,7,3’,4’,5’-pentahydroxyflavone, apigenin 7-cellobioside, catechin 3-o-gallate/epigallocatechin gallate efektif terhadap aktivitas enzim a-glukosidase sebagai antihiperglikemia. Kata Kunci: Flavonoid, Averrhoa Bilimbi L, a-Glukosidase, In Silico, Anti Hiperglikemia